The Altered Behavioural Responses Displayed by Litter Rats After Chronic Administration of Non-Toxic Concentrations of ZnTe to Parent Rats Are Reversed by Simultaneous Folic Acid Treatment - Ratti, Silvia Gabriela (2015)
Trace elements are an omnipresent group of chemical elements that are present practically in all types of environments sustaining life. Since its principal characteristic is the very low concentration in ground and water, it was thought that its importance to metabolic processes to the living cell was minimal. However, in the past 15 years knowledge has been accumulated regarding that these chemical elements have important influences on the cell dynamic homeostatic mechanisms. Previous evidence from our laboratory has shown that chronic administration of ZnTe to pregnancy, delivery and subsequent juvenile stages in rats affected several of its behavioural parameters related to motivated, lateralized exploration, social and defensive behaviour. In the third part of this study, the possible effect of folic acid (FolA) on the Te-induced behavioural changes was studied. Three experimental groups were formed, Control, animals treated with tap water; ZnTe, animals treated with the trace elements, and ZnTe+FolA, animals treated with the combination of ZnTe and FolA, in the same way that of the previous experiments. Results show the folic acid treatment did not counteract the increase of motor activity observed in those animals treated with ZnTe. However, in the exploration induced by novelty measured in the Double Lateral Hole-board Labyrinth, the corridor behavioural activity displayed by animals under the combination of FolA and ZnTe was similar to control and significantly different from the ZnTe-treated group. The left exploration bias naturally present in control, and blocked in the ZnTe-treated animals, was restored to control values in the FolA+ZnTe treated animals. A similar observation was found with the percentage of animals with left-bias exploration, where those rats treated with the combination of FolA and ZnTe reached similar values to control and significantly greater than the ZnTe-treated rats which were statistically lower than control. Social behaviour, inhibited by ZnTe was restored to normal in the FolA treated animals. A similar observation was found in the defensive behaviour test. Results are compatible with the idea that FolA, which is known as a methyl donor reagent, can restore the behavioural effects of ZnTe, giving support to previous results suggesting that trace elements could act by molecular mechanisms involving epigenetical modulation of DNA.